2022
DOI: 10.1101/2022.04.22.489234
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dual RNA-seq reveals a type 6 secretion system-dependent blockage of TNF-α signaling and BicA as a Burkholderia pseudomallei virulence factor important during gastrointestinal infection

Abstract: Melioidosis is a disease caused by the Gram-negative bacillus Burkholderia pseudomallei (Bpm), commonly found in soil and water of endemic areas. Naturally acquired human melioidosis infections can result from either exposure through percutaneous inoculation, inhalation, or ingestion of soil-contaminated food or water. Our prior studies recognized Bpm as an effective enteric pathogen, capable of establishing acute or chronic gastrointestinal infections following oral inoculation. However, the specific mechanis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 57 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…Previously, we examined the virulence of ΔbicA in both acute and chronic models of gastrointestinal infection (1) and found that although ΔbicA demonstrated attenuation, those infection models are not able to discern the specific role of macrophages during infection. To The copyright holder for this preprint (which this version posted July 10, 2023. ; https://doi.org/10.1101/2023.07.10.548404 doi: bioRxiv preprint high titers in both lungs and spleen and the spleen was enlarged with visible abscesses, this gross pathology is common in spleens chronically infected with WT Bpm (22).…”
Section: Bica Required For Proficient Intracellular Replication In Ma...mentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we examined the virulence of ΔbicA in both acute and chronic models of gastrointestinal infection (1) and found that although ΔbicA demonstrated attenuation, those infection models are not able to discern the specific role of macrophages during infection. To The copyright holder for this preprint (which this version posted July 10, 2023. ; https://doi.org/10.1101/2023.07.10.548404 doi: bioRxiv preprint high titers in both lungs and spleen and the spleen was enlarged with visible abscesses, this gross pathology is common in spleens chronically infected with WT Bpm (22).…”
Section: Bica Required For Proficient Intracellular Replication In Ma...mentioning
confidence: 99%
“…All experiments were conducted with the prototypical wild-type strain of Burkholderia pseudomallei K96243 or derivative strains (K96243 ∆bicA, K96423 ∆bicA::bicA). K96243 ∆bicA and K96423 ∆bicA::bicA were constructed in (1). All strains were routinely grown at 37°C on LB agar plates and in LB broth with shaking.…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
See 2 more Smart Citations